Analysis of the semi-empirical Stark broadening methods to improve the line emission accuracy: applications on He, Ar and Fe thermal plasmas. (27th July 2018) - Hannachi, R; Cressault, Y; Teulet, Ph; Béji, L
Abstract: Stark broadening of isolated lines plays a crucial role in the calculation of radiative transfer of thermal plasmas. The most popular methods used are: the simple formula based on the semi-empirical method developed by Griem; the more elaborated method of Dimitijević and Konjević and the well–known Lindholm formula. Their accuracy are investigated through comparisons of obtained Stark widths with previous experimental and theoretical results for HeI, ArI, ArII, ArIII, FeI and FeII lines at different temperatures and electron number density values. An improvement of the calculated Stark results is proposed and discussed by adding an empirical correction factor to the proposed formulas. All the calculated factors are supplied in tables in order to use them in the calculation of radiative properties of thermal plasmas. The influence of the Stark models and of the empirical correction factors in the calculation of the net emission coefficient (NEC) of line are analyzed and discussed for pure helium, argon and iron plasmas, in a temperature range from 0.3 kK to 30 kK, and the atmospheric pressure. The obtained results show that the effect of the empirical correction factor does not exceed 31% but the choice of the proposed Stark broadenings models can induce huge variations in line radiation.